Developing intercultural competence in a 'comfortable' third space: postgraduate studies in the UK. (2nd January 2019) - McKinley, Jim; Dunworth, Katie; Grimshaw, Trevor; Iwaniec, Janina
ABSTRACT: With the number of international postgraduate students in UK universities steadily increasing, there is great interest in understanding how institutions can more effectively meet these students' expectations and needs through programme-supported development of intercultural competence. This paper reports on a project that explored experiences and perceptions of the development of intercultural competence in a UK higher education context. Academic staff ( N  = 8) and international postgraduate students ( N  = 24), from a range of countries, were recruited for preliminary interviews (two staff from each of the four faculties), focus groups (students of these staff), and stimulated recall interviews (same staff). The project targeted tensions and issues occurring between the perspectives of participants. It focused on the performance and negotiation of identities in the 'third space' that emerged between participants using different cultural discourses. The findings suggest that, despite the inherent contradiction of comfort and the conflict of negotiation, efforts are made by both students and staff to create a 'comfortable' third space in which to negotiate learning. By this we mean an environment in which to negotiate learning where those present feel at ease with their own and others' cultural identities and differences. This raises significant implications for policies and practices regarding the development of intercultural competence. Specifically, the university needs to build a better understanding of how to create a 'sphere of interculturality' in which international postgraduate learning can take place.